Geo-service Industry Analysis: Scanning Challenges and Opportunities for Sustainable Asia-Pacific - Tamer Zaki Fouad Mohamed (Journal of Business and Behavioural Entrepreneurship, 2017)
Global environmental risks resulted mainly from irresponsible industrial policies and polution, have a destructive impact on economies and societal wellbeing, especially in the Asia-Pacific. The Geoservice industry is increasingly contributing to global sustainability and welfare by providing many solutions to environmental and socio-economic issues. The industry is growing fast in the Asia-Pacific, yet there are various issues hindering industry and technology diffusion as well as many opportunities which can be harvested for better industry growth. There is much confusion and lack of studies on this new growing industry, therefore the paper attempts to simplify and clarify the structure and interdeciplinary concept of geoservices. The purpose of this study is to explore and assess the opportunities and threats influencing geoservice industry growth and diffusion in the Asia-Pacific. Methodology of such analytical descriptive study relied on secondary data and baseline information to examine and understand the industry issues and characteristics in the region. The paper also adopted various industry analysis and assessment tools such as PESTLE, Porter and Strategic Grouping analysis to support decision makers in considering the challenges and opportunities for investment and engagement in that industry. The key contribution and significance is to promote and raise awareness among general public, government and non government stakeholders on the issues hindering geospatial industry diffusion as prerequisite for sustainability in the Asia-Pacific. The paper also suggested solutions and recommendations for decisionmakers to foster industry diffusion and understand opportunities for investment.